Development Model of Child-Friendly Management in Islamic Boarding Schools (Pesantren) - Izzah, Nuril; Ahmad, Masduki; ., Suryadi (Journal of Posthumanism, 2025)
This study aims to examine and formulate a model of family-based child-friendly pesantren (Islamic boarding school) management at three pesantren: Daarul Mutaqien Parung, Darunnajah Cipining, and Sahid Gunung Menyan Bogor. These pesantren demonstrate a strong commitment to creating a safe, humanistic, and violence-free educational environment, both physically and verbally. The approach used includes participatory and integrative patterns by involving all stakeholders in the planning, organization, implementation, and evaluation of policies and educational as well as caregiving programs. This research adopts a qualitative approach with a case study design. Data collection methods include observation, questionnaires, interviews, and document analysis. The data analysis techniques consist of data collection, data reduction, data display, conclusion drawing, and verification. Data validity was ensured through credibility, transferability, dependability, and confirmability. The findings of this study indicate that planning based on Islamic values, strengthening the caregiving role, and synergy between pesantren and families are key factors in preventing violence against students. Clear organizational structures, strict supervision through monitoring systems and CCTV, and active parental involvement further enhance the effectiveness of child-friendly pesantren implementation. This study offers a model of child-friendly pesantren management that can serve as a reference in developing a more inclusive Islamic education system that prioritizes the protection of children’s rights.